Survival in a Concentrating Industry: The Case of Daily Newspapers in the Netherlands - Hans L. van Kranenburg; Franz Palm; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2002)
This paper studies the effects of aggregate, industry-, and firm-specific factors on the exit hazard rates in the market for daily newspapers in The Netherlands from 1950 to 1996. We present a brief overview of the exit literature. On the basis of the existing empirical evidence, we decided to specify and estimate exponential and piecewise constant hazard rate models. We find that exit hazards of daily newspapers depend on the circulation size, ownership, and number of incumbents. Moreover, the effects are time-dependent. We do not find any significant effect of macroeconomic factors.
Keywords: L13; D21; L82; L16; C41; 330; scale economies; survival chances; concentrating industry; newspapers; Zeitungsverlag; Marktaustritt; Industrieökonomik; Schätzung; Niederlande